2022
DOI: 10.1590/1981-6723.16821
|View full text |Cite
|
Sign up to set email alerts
|

Expeller pressing of passion fruit seed oil: Pressing efficiency and quality of oil

Abstract: The passion fruit juice production generates around 70% of by-products comprising rind, seeds and arils that are commonly discarded. The seeds consist of 4% of fruit weight with the potential to produce around 2,500 ton/year of high added-value oil in Brazil. In this work, passion fruit seeds from different juice manufacturers and the effect of the seed moisture were evaluated towards oil quality and extraction efficiency, using a continuous expeller press of 100 kg/h capacity. The seeds were washed and dried … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Seed moisture is a parameter that can be measured and changed as needed. An important factor in optimising the process of pressing oilseeds is to determine the most effective humidity indicator, at which the oil yield is the highest (Antoniassi et al, 2022). Based on the research of many scientific papers, the study (Bălțatu et al, 2022) concluded that there is an optimal humidity level for each type of oilseed.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Seed moisture is a parameter that can be measured and changed as needed. An important factor in optimising the process of pressing oilseeds is to determine the most effective humidity indicator, at which the oil yield is the highest (Antoniassi et al, 2022). Based on the research of many scientific papers, the study (Bălțatu et al, 2022) concluded that there is an optimal humidity level for each type of oilseed.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Efficiency [2] of the screw press for oil extraction is another important aspect of the production process. The auger plays a key role in pressing [1], ensuring efficient squeezing of oil from the raw material.…”
Section: Introduction / вступmentioning
confidence: 99%
“…Despite the popularity of passion fruit consumption, approximately 70% of the by-products produced during passion fruit juice production are discarded (7). However, extracts from waste have shown medicinal effects and a wide range of pharmacological activities against non-communicable diseases, including anti-diabetic, anti-cancer, wound repairing, anti-inflammatory, hypolipidemia, hypertensive capacities (8)(9)(10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%